Clonidine withdrawal induced sympathetic surge. (2nd June 2015) - Shaw, Michael; Matsa, Ramprasad
Abstract : A 30-year-old man with a history of epilepsy and substance misuse presented to the hospital with status epilepticus. Difficult seizure control necessitated anaesthetising the patient followed by intubation and ventilation. A clonidine infusion was started as the patient developed withdrawal syndrome and was difficult to wean off mechanical ventilation. Once the withdrawal syndrome was controlled, the clonidine was abruptly stopped. Two hours after stopping the infusion, the patient developed high-grade fever, severe hypertension, tachycardia, profound sweating and lacrimation. The patient then developed respiratory distress syndrome secondary to acute pulmonary oedema. Clonidine withdrawal as a cause of such response was proposed. Reversal of symptoms and successful reweaning was achieved by restarting a low-dose clonidine infusion followed by slow downward titration and use of oral clonidine as a step-down measure. The patient was subsequently discharged from the intensive care unit.